Eilat virus displays a narrow mosquito vector range - Farooq Nasar; Andrew D Haddow; Robert B Tesh; Scott C Weaver (Parasites & Vectors, 2014)
Abstract Background Most alphaviruses are arthropod-borne and utilize mosquitoes as vectors for transmission to susceptible vertebrate hosts. This ability to infect both mosquitoes and vertebrates is essential for maintenance of most alphaviruses in nature. A recently characterized alphavirus, Eilat virus (EILV), isolated from a pool of Anopheles coustani s.I. is unable to replicate in vertebrate cell lines. The EILV host range restriction occurs at both attachment/entry as well as genomic RNA replication levels. Here we investigated the mosquito vector range of EILV in species encompassing three genera that are responsible for maintenance of other alphaviruses in nature. Methods Susceptibility studies were performed in four mosquito species: Aedes albopictus, A. aegypti, Anopheles gambiae, and Culex quinquefasciatus via intrathoracic and oral routes utilizing EILV and EILV expressing red fluorescent protein (−eRFP) clones. EILV-eRFP was injected at 107 PFU/mL to visualize replication in various mosquito organs at 7 days post-infection. Mosquitoes were also injected with EILV at 104-101 PFU/mosquito and virus replication was measured via plaque assays at day 7 post-infection. Lastly, mosquitoes were provided bloodmeals containing EILV-eRFP at doses of 109, 107, 105 PFU/mL, and infection and dissemination rates were determined at 14 days post-infection. Results All four species were susceptible via the intrathoracic route; however, replication was 10–100 fold less than typical for most alphaviruses, and infection was limited to midgut-associated muscle tissue and salivary glands. A. albopictus was refractory to oral infection, while A. gambiae and C. quinquefasciatus were susceptible only at 109 PFU/mL dose. In contrast, A. aegypti was susceptible at both 109 and 107 PFU/mL doses, with body infection rates of 78% and 63%, and dissemination rates of 26% and 8%, respectively. Conclusions The exclusion of vertebrates in its maintenance cycle may have facilitated the adaptation of EILV to a single mosquito host. As a consequence, EILV displays a narrow vector range in mosquito species responsible for the maintenance of other alphaviruses in nature.